(untitled) (Research, Society and Development, 2024)
This article aims to analyze the transition from the Family Health Support Center (NASF) to the eMulti Program, highlighting structural, operational, and financial challenges, as well as the impacts of this change on Primary Health Care (PHC). This is a qualitative study with a bibliographic approach, based on academic literature, official documents, and technical reports. The results indicate that, although NASF promoted a multiprofessional approach to healthcare, it faced significant limitations related to insufficient funding and coordination. The eMulti program emerges as an attempt to overcome these gaps, offering greater flexibility and autonomy to municipalities. However, obstacles such as the absence of clear guidelines, professionals’ adaptation difficulties, and funding challenges persist. It is concluded that eMulti represents progress in the multiprofessional care model but requires efforts to enhance team integration, collaboration, and effectiveness. This study contributes to the debate on public health policies and suggests directions for future research.